Intramural Bowel Hematoma Presenting as Small Bowel Obstruction in a Patient on Low-Molecular-Weight Heparin. (13th June 2018) - Choi, Beatrix Hyemin; Koeckert, Michael; Tomita, Sandra
Abstract : There is increasing use of low-molecular-weight heparin (LMWH) for treatment of pediatric thromboembolic disease as it has been shown to be safe and effective. It has several advantages over unfractionated heparin, such as reduced need for monitoring, easier route of administration, decreased risk of heparin-induced thrombocytopenia, and lack of drug-drug interactions. Nevertheless, LMWH still poses a bleeding risk as with any anticoagulant therapy. We present the case of a 4-year-old boy who was placed on LMWH for a catheter-related deep venous thrombosis in the setting of intractable seizures and subsequently developed a small bowel obstruction secondary to a suspected intussusception. He underwent exploratory laparotomy and was found to have an intramural bowel hematoma. Prior to this bleed, the patient had been monitored daily, and his anti-Xa levels were found to be in the therapeutic range. This case highlights the need for a high index of suspicion for spontaneous bleeding even in the setting of therapeutic anti-Xa levels.